A 24-hour Assessment of Lifestyle Constraint in Stroke Survivors - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Stroke often comes with a spectrum of constraints to lifestyle. This study investigated these constraints using a 24-hour lifestyle assessment among 6 stroke survivors.Objectives:The objective of this study was to provide an understanding of the ways in which stroke survivors are experiencing stroke, along with the opportunities and challenges of everyday life.Materials and Methods:Six stroke survivors were recruited to participate in this qualitative study. The study participants were 3 males and 3 females. Participants were engaged in in-depth interviews to generate information regarding the objective of this study. The interview was recorded on audiotape and transcribed. The generated data were analysed by thematic framework analysis.Results:Findings showed that 5 out of the 6 stroke survivors faced challenges in everyday life, in reconstructing their identity and depended on their family members to take care of them. All the stroke survivors reported some form of functional restrictions, with 4 out of the 6 responents indicating that their movement was restricted to their immediate compound and 5 out of the 6 respondents indicating that they were unable to do most of their house-hold chores; and one respondent said that he 'barely could do anything for self'.Conclusion and Recommendations:Among the 6 respondents, stroke has several manifestations on patients' mobility and indepdence. These have significant bearing on their wellbeing. Studies with larger sample sizes incorporating quantitative methods and longitudinal follow-up are recommended to shed more light on these findings.